State of Maine. In Senate, February 8, 1827 : the Committee to whom was referred a "Resolve respecting the accounts of the managers of the Sullivan Bridge Lottery, " have taken the same into their consideration . ([publisher not identified], 1827)
February 8, 1827 Report of the Senate Committee on the Sullivan Bridge Lottery. After reviewing the circumstances surrounding the petition to have this lottery, the committee determined that there was neither a sufficient legal nor equitable reason for passage.